Foreign Exchange Market Structure, Players and Evolution - Michael R. King; Carol Osler; Dagfinn Rime (Norges Bank, 2011)
Electronic trading has transformed foreign exchange markets over the past decade, and the pace of innovation only accelerates. This formerly opaque market is now fairly transparent and transaction costs are only a fraction of their former level. Entirely new agents have joined the fray, including retail and high-frequency traders, while foreign exchange trading volumes have tripled. Market concentration among dealers has risen reflecting the heavy investments in technology. Undeterred, some new non-bank market participants have begun to make markets, challenging the traditional foreign exchange dealers on their own turf. This paper outlines the players in this market and the structure of their interactions. It also presents new evidence on how that structure has changed over the past two decades. Throughout, it highlights issues relevant to exchange rate modelling.
hdl:11250/2496951
Keywords: F31; G12; G15; C42; C82; 330; exchange rates; algorithmic trading; market microstructure; electronic trading; high frequency trading